The effects of mycotoxin deoxynivalenol (DON) on haematological and biochemical parameters and selected parameters of oxidative stress in piglets - Modra, Helena; Blahova, Jana; Marsalek, Petr; Banoch, Tomas; Fictum, Petr; Svoboda, Martin (Neuro endocrinology letters, 2013)
OBJECTIVES: Deoxynivalenol (DON) - trichothecene mycotoxin, is frequently detected in high concentrations in cereals in the temperate region of Europe. The aim of this study was to determine the effect of DON in feed on haematological and biochemical parameters and on oxidative stress in piglets. METHODS: Two concentrations of DON in feedstuff for pigs were chosen: 0.6 mg/kg (group C) and 2.0 mg/kg (group M). Twelve weaned pigs were used in each group. Pigs were fed with naturally contaminated feed for 4 weeks. On days 14, 21 and at the end of the experiment (day 28) samples of blood were taken to determine haematological parameters, plasma biochemical parameters, ceruloplasmin activity and FRAP (ferric reducing ability of plasma). RESULTS: The haematological variables did not show changes in response to contaminated diet with exception of the mean corpuscular volume, which was significantly decreased at the end of the experiment in the group M. A significant increase of alkaline phosphatase activity (140%, p<0.01) was found in the group M compared to the group C at the end of the experiment. A significant decrease was found on the day 21 in FRAP (85%, p<0.001) and on the day 28 in ceruloplasmin (75%, p<0.01) in the group M compared to the group C. CONCLUSIONS: The decrease of FRAP and ceruloplasmin indicate a lowered ability of organism to scavenge reactive oxygen species. The higher concentration of DON in feedstuffs had a negative influence on the antioxidant ability of piglet's plasma.
Keywords: Animals; Mycotoxins; novorozená zvířata; Female; biologické markery; oxidační stres; Biomarkers; ženské pohlaví; Food Contamination; Animal Feed; Oxidative Stress; Animals, Newborn; prasata; mykotoxiny; Blood Proteins; krevní proteiny; kontaminace potravin; Trichothecenes; Male; Swine; trichotheceny; krmivo pro zvířata; zvířata; mužské pohlaví